Conformation Controls Mobility: 2H‐Tetranaphthylporphyrins on Cu(111). Issue 5 (17th February 2020) - Kuliga, Jan; Massicot, Stephen; Adhikari, Rajan; Ruppel, Michael; Jux, Norbert; Steinrück, Hans‐Peter; Marbach, Hubertus
Abstract: The adsorption behavior and the mobility of 2H‐Tetranaphthylporphyrin (2HTNP) on Cu(111) was investigated by scanning tunneling microscopy (STM) at room temperature (RT). The molecules adsorb, like the structurally related 2HTPP, in the "inverted" structure with the naphthyl plane restricted to an orientation parallel to the Cu surface. The orientation of the four naphthyl groups yields altogether 16 possible conformations. Due to the existence of rotamer pairs, 10 different appearances are expected on the surface, and all of them are identified by STM at RT. Most interestingly, the orientation of the naphthyl groups significantly influences the diffusion behavior of the molecules on Cu(111). We identify three different groups of conformers, which are either immobile, medium or fast diffusing at RT. The mobility seems to decrease with increasing size of the footprint of the conformers on the surface. Abstract : Mobile or not ? 2H‐Tetranaphthylporphyrin adsorbs as ten different conformers on Cu(111) at RT. The orientation of the naphthyl groups controls the diffusion behaviour of the molecules, from immobile to medium and fast.